From jogging to ka-ching! / Haslina Hassan and Wani Nurfahani Mohd. Sapuan - Hassan, Haslina; Mohd. Sapuan, Wani Nurfahani (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Opening my Facebook late last night, I saw a success story posted by a friend of how she dropped one dress-size. On my Twitter, I saw a stranger recommending his diet to reduce his waistline. Moving to TikTok, an influencer is promoting a healthy lifestyle to lose weight. In this body-conscious world, everyone is sharing their go-to method for losing weights, and these are all considered recreational activities to some. Nothing beats the feeling of working up a sweat after a long day stuck at your desk, squeezing your brain juices. As the cost of living increases at the speed of light while the minimum wage increases at the pace of a snail, it leaves us no time to enjoy that post-workout sweat. So, people are looking for recreational activities with the potential of being “side hustles”. Though it might be a great idea mixing business with pleasure this time around, we really need to be careful of the drug of our choice. It could be a blessing in disguise or a poisoned gift to some. There are three main ways to earn money through recreational activities.